Sources Of Growth In The Manusfacturing Sector In Malaysia: Evidence From Ardl And Structural Decomposition Analysis - Kamaruddin, Rohana; Masron, Tajul Ariffin (Asian Academy of Management (AAM), 2010)
The manufacturing industry has been an important sector in the Malaysian economy for the past three decades. The important role of this industry to the Malaysian economy today is not only because Malaysia depends substantially on manufacturing for its foreign exchange earnings, but also because Malaysia is the main exporter of electrical and electronic products. This study examines the structural changes in the Malaysian economy by utilising two economics tools, namely, the econometric approach using the Autoregressive Distributed Lag (ARDL) model and the input-output approach using Structural Decomposition Analysis (SDA). These two approaches are used to analyse the sources of growth in the manufacturing sector in Malaysia. From both economic approaches, ARDL and IO, the results agreed on the importance of the domestic consumption effect as a source of growth in the economy. The empirical results from this study are very useful guide to the manufacturing industry for the need to generate more domestically oriented products.